1999
DOI: 10.1103/physreva.60.2018
|View full text |Cite
|
Sign up to set email alerts
|

KαandKβx-ray emission spectra of metallic scandium

Abstract: The K␣ and K␤ spectra from metallic scandium, the first of the 3d transition elements, were measured using a high-resolution curved crystal spectrometer. The spectrometer resolution was determined employing a narrow emission line from pionic neon. The parameters of the resolution-corrected spectrum are extracted and compared to previous studies and theory. Fits to ab initio relativistic Dirac-Fock calculated spectra show that the K␣ spectrum can be accounted for using an isolated-atom model with diagram, 3d-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 48 publications
3
47
1
Order By: Relevance
“…It was reported that the approach of addressing only the width and asymmetry of a line, is not convenient to account for the shapes of complex spectra such as those of the 3d transition metals [45]. Anagnostopoulos et al [46] calculated the [1s3p] and [1s3d] shake probabilities in Sc and found 15 and 38 %, respectively. Moreover, Lowe et al [47] calculated the shake probability of the double electrons transition in order to elucidate the [1s3d] contribution in 3d elements.…”
Section: Energies and Linewidths Of Kα And Kβ Transitionsmentioning
confidence: 99%
“…It was reported that the approach of addressing only the width and asymmetry of a line, is not convenient to account for the shapes of complex spectra such as those of the 3d transition metals [45]. Anagnostopoulos et al [46] calculated the [1s3p] and [1s3d] shake probabilities in Sc and found 15 and 38 %, respectively. Moreover, Lowe et al [47] calculated the shake probability of the double electrons transition in order to elucidate the [1s3d] contribution in 3d elements.…”
Section: Energies and Linewidths Of Kα And Kβ Transitionsmentioning
confidence: 99%
“…In practice, however, it is useful to assign probabilities to a set of quantum numbers, as calculation of satellite energies generally proceeds by assuming the shake-off electron can be localized to a particular subshell [34][35][36][37]. To this end, we adopt the following procedure for assigning shake-off probabilities to subshells:…”
mentioning
confidence: 99%
“…In generating the CSF basis, single and double excitations were allowed from the 3p, 3d, and 4s subshells to virtual orbitals up to the n = 5 060501-2 1. (Color online) Current theoretical probability of shake-off from 3d subshell (solid line) compared to prior theory (dotted line) [22], (dashed line) [24], and experimental results (points). Symbols [38], [28], [35], • [39], [36], [37], [34], and x [28] denote probability of shake-off from 3d subshell following 1s ionization. Two types of experimental results are presented: Multiconfiguration fits (solid points) use atomic calculations to deconvolve the raw experimental spectrum, while phenomenological fits (hollow points) use a series of arbitrary Lorentzians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Placing the X-ray source at about the focal position R · sin B with the reflection centered on the target yields S S ≈ 0.3 mm·50 mm (25 mm) 2 π ≈ 10 −2 for a source diameter of 5 cm. Exotic atom X-ray transitions from the intermediate part of the atomic cascade, e. g.,pHe(5 − 4) andpNe(13 − 12) [15] or π Ne(6 − 5) [19], have been used for the determination of the response function. For ultimate crystal performance studies, however, count rates available from exotic atoms are not sufficient.…”
Section: Methodsmentioning
confidence: 99%